FORMYLATION OF 2-(METHYLTHIO)PYRIMDINE-4,6-DIOL IN THE REACTIO CONDITIONS OF VILSMEIER-HAAK (SHORT MESSAGE) - E. S. Ofitserova; A. A. Shklyarenko; I. P. Yakovlev; E. V. Fedorova (Разработка и регистрация лекарственных средств)
The reaction of formylation by Vilsmeier - Haack was held. The effect of excess phosphorus oxychloride in the direction of the reaction. Optimal conditions were conducting formylation reaction to obtain a single compound with a high yield. The result of the reaction product mixture was conducted chromatographic separation on a column packed with silica gel 60 Silica.